Climate and plant structure determine the spatiotemporal butterfly distribution on a tropical mountain. (16th October 2020) - Beirão, Marina V.; Neves, Frederico S.; Fernandes, G. Wilson
Abstract: Mountains are among the most powerful natural gradients for testing ecological and evolutionary responses of biota to environmental influences because differences in climate and plant structure occur over short spatial scales. We describe the spatiotemporal distribution patterns and drives of fruit‐feeding butterfly diversity in the mountainous region of Serra do Cipó, Minas Gerais, Brazil. Seven elevations from 822 to 1, 388 m a.s.l. were selected for evaluating the effects of abiotic factors and vegetation characteristics on butterfly diversity. A total of 44 fruit‐feeding butterfly species were recorded in a two‐year study. Species richness (local and regional) of fruit‐feeding butterflies decreased with increasing elevation. The interaction between temperature or humidity and precipitation influenced the abundance and β‐diversity of butterflies in the elevation gradient, whereas β‐diversity decreased with increasing plant richness. Butterfly richness (local and regional) and β‐diversity varied with the sampling period, with fewer species in July (2012 and 2013), the dry period, as expected for Neotropical insects. β‐Diversity in space and time was due to species replacement (turnover), indicating that butterfly composition differs throughout the mountain and over time. In summary, climate and plant richness largely influence butterfly diversity in the elevational gradient. Climatic changes in conjunction with increasing anthropic impacts on mountainous regions of southeast Brazil will likely influence the community of mountaintop butterflies in the Espinhaço Mountain Range. Abstract in Portuguese is available with online material. RESUMO: As montanhas estão entre os mais poderosos gradientes para testar as respostas ecológicas e evolutivas da biota em relação influencias ambientais pois as diferenças no clima e na estrutura vegetal ocorrem em pequenas escalas. Nós descrevemos o padrão de distribuição espaço‐temporal de borboletas frugívoras em uma montanha situada na Serra do Cipó, Minas Gerais, Brasil. Foram selecionadas sete elevações, de 822 a 1.388 m para avaliação dos efeitos abióticos e de vegetação na diversidade de borboletas. Um total de 44 espécies de borboletas frugívoras foram coletadas em dois anos de estudo. A riqueza de espécies (local e regional) diminuiu com o aumento da elevação. A interação entre temperatura ou umidade e a precipitação influenciou a abundancia e a diversidade β, enquanto que o aumento da riqueza das espécies de plantas diminuía a diversidade β. A riqueza de borboletas (tanto local quanto regional) e a diversidade β variaram ao longo dos períodos amostrados, com menos espécies em julho, período de inverno e seco, como previsto pra insetos da região Neotropical. A decomposição da diversidade β revelou que tanto a variação espacial quanto a temporal ocorreu por substituição de espécies, indicando que a composição das borboletas varia espacialmente ao longo do gradiente e temporalmente. Em resumo, o clima e a riqueza de espécies vegetais influenciam a diversidade de borboletas em um gradiente altitudinal. Com as mudanças climáticas juntamente com o aumento dos impactos antrópicos nas regiões montanhosas do sudeste Brasileiro possivelmente influenciarão as comunidades de topo de borboletas na Serra do Espinhaço.